Correlation dependencies in the motivational component of personal and professional municipal employees’ qualities - S. K. Khaidov (Вестник университета, 2023)
The article is devoted to the research of the motivational component of municipal employees’ personal and professional qualities. It reveals their concept, content and role in the functioning of local self-government bodies. The correlation and interdependence of municipal functions is shown, the professional activity of municipal employees and its psychological content in the management of municipalities are presented. The research relevance is due to the complexity of socio-political situation for Russia in modern conditions, where the implementation productivity of state tasks at the local level of government largely depends on municipal servants. The study purpose is to establish the relationship between the indicators in the motivational component of municipal employees. The identified results of the empirical research indicate the presence of multiple interrelations between the indicators of the motivational component, indicating their organization and consistency, which makes it possible to recommend further ways and directions for development of the above qualities to improve the functioning productivity of local government productivity.